Selective detection of Fe3+, Cr3+ and Cu2+ in water using highly luminescent Gd2O3:Eu3+ nanoparticles - Ghosh, Debasish; Luwang, Meitram Niraj (Journal of Luminescence, 2016)
Rod shaped Eu3+ doped Gd2O3 nanoparticles were synthesised by a simple wet-chemical method followed by high temperature heating at 700 degrees C. The nanoparticles were characterised by X-ray diffraction (XRD), infra-red (IR), transmission electron microscopy (TEM), x-ray photonelectron spectroscopy (XPS), photoluminescence (PL) studies and lifetime measurement. The particles show strong host sensitised luminescence in water. Luminescence in water is selectively quenched by Fe3+, Cr3+ and Cu2+ ions. This luminescence quenching phenomenon has been utilised to detect metal ions in synthetic water and environmental water samples. Results obtained by luminescence quenching for environmental water samples are in good agreement with the results obtained from inductively coupled plasma atomic emission spectroscopy (ICP-AES) study. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Detection; Luminescence; Nanoparticles; Quenching; Sensitization